Performing Peace and Friendship : The World Youth Festivals and Soviet Cultural Diplomacy. - Koivunen, Pia. (Rethinking the Cold War Series, 2022)
The peer-reviewed series offers books that illuminate the multifaceted history of the Cold War in both its European and Global dimensions, across and beyond the Iron Curtain. It focuses on the interactions, interdependencies and co-operation of Eastern state socialist countries (and their citizens) with Western capitalist, Latin American, African and non-aligned states (and their citizens), as well as with China.